Simplifying The Big Mac Index1. (20th August 2016) - Clements, Kenneth W.; Si, Jiawei
Abstract: The Economist magazine recently introduced a major innovation to its famous Big Mac Index of currency values by adjusting for differences in incomes of countries. A recent paper (O'Brien and Ruiz de Vargas, 2017, OR) explains clearly the workings of the new index, something overlooked by The Economist. The current article draws on OR to suggest an alternative formulation that is attractive in its simplicity.